The relationship between student-teacher relationship quality, preschool children's prosocial behaviour and parental involvement - Nur Liyana Shamsudin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Student-teacher relationship quality and parental involvement promote prosocial behaviour in preschool children. The aim of the study is to investigate the relationship between student-teacher relationship quality, preschool children's prosocial behaviour, and parent involvement. This study hypothesized that (1) the higher the score in the student-teacher relationship scale, the higher the score in prosocial behaviour; (2) the higher the parental involvement, the higher the score on children's prosocial behaviour scale; (3) and student-teacher relationship quality will mediate the relationship between parental involvement and preschool children's prosocial behaviour. 197 preschool children (aged between 55 months to 84 months) participated in the study, who are enrolled in 'prasekolah' (preschool) in public schools in Selangor. Parents and teachers represent the children and rate the questionnaires that consist of the student-teacher relationship scales-short form (STRS-SF), the Adaptive Social Behavior Inventory (ASBI) and the Family Involvement Questionnaire (FIQ). The data was analyzed using regression analysis. The analysis employed the Baron and Kenny's (1986) three-procedure approach and Preacher and Hayes's (2004) bootstrapping techniques to determine mediation. The results from the bootstrapping techniques found that the low levels of conflict in student-teacher relationship mediate the relationship between parental involvement and prosocial behaviour. The result suggests that preschool children may have prosocial behaviour when parents are involved with them at home and school through a low level of conflict relationship with their teachers. The discussion of the implications and limitations of the present study are also provided.